2019
DOI: 10.1101/863589
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ex vivo and in vivo imaging of mouse parietal association cortex activity in episodes of cued fear memory formation and retrieval

Abstract: The parietal cortex in rodents has an integrative function and participates in sensory and spatial processing, movement planning and decision-making. However, much less is known about its functions in associative memory processing. Here using Fos immunohistochemical mapping of neuronal activity and two-photon imaging in Fos-eGFP mice we show an involvement of anterior part of the parietal cortex (PtA) in the formation and retrieval of recent fear memory in mice. Using ex vivo c-fos imaging we demonstrate the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The similar result has been observed in the previous published study that changes in c-Fos were observed but no changes in neuronal activity were observed by in vivo electrophysiological recording (Yao et al, 2020). Although c-Fos, an intermediate early gene that serves as a molecular marker of neuronal activation (Ivashkina et al, 2021), it is expressed only in some kinds of neurons following peripheral stimulation, which might be inducible only in neurons that contain a particular neurotransmitter, that produce a particular kind of action potential, or that possess particular kinds of receptors. Therefore, it may be an incomplete marker for responsive activity (Bullitt, 1990).…”
Section: Discussionsupporting
confidence: 90%
“…The similar result has been observed in the previous published study that changes in c-Fos were observed but no changes in neuronal activity were observed by in vivo electrophysiological recording (Yao et al, 2020). Although c-Fos, an intermediate early gene that serves as a molecular marker of neuronal activation (Ivashkina et al, 2021), it is expressed only in some kinds of neurons following peripheral stimulation, which might be inducible only in neurons that contain a particular neurotransmitter, that produce a particular kind of action potential, or that possess particular kinds of receptors. Therefore, it may be an incomplete marker for responsive activity (Bullitt, 1990).…”
Section: Discussionsupporting
confidence: 90%
“…An interesting technique to reduce this problem is the use of viral-based TRAP (targeted recombination in active populations) to express GCaMP only in the neurons which were naturally active during the task (Matos et al, 2019). Especially for miniscope studies, the utilization of Fos-Cre-GCaMP systems (Ivashkina et al, 2019) to assess longterm changes only in neurons that are related to a task holds a lot of promise for specifically associating shifts in neuronal activity to changes in behavior.…”
Section: Engram-specific Taggingmentioning
confidence: 99%
“…The role of the mPFC is an instantiation of the importance of association cortices in the integration of information from lower hierarchical structures. It is possible that ensemble maturation in other association cortices, such as the parietal cortex (Ivashkina, Gruzdeva, Roshchina, Toropova, & Anokhin, 2019), or even in a cortex-wide dispersed-ensemble fashion (Roy et al, 2019).…”
Section: Conclusion and Perspectives For The Fieldmentioning
confidence: 99%